Description of Gross Motor Development Children After Taekwondo Training at Dojang Balai Gadang - Annisa Zukhrufa Isnani; Setiawati Setiawati (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
This research is motivated by the low gross motoric skills of children, this is presumably due to the lack of children's gross motor movement exercises that are carried out at home. This study aims to see a description of the gross motor development of children aged 6 to 8 years after participating in taekwondo training at Dojang Balai Gadang, Balai Gadang Village, Koto Tangah District, Padang City. The type of research approach is quantitative with descriptive method. The population of the study was children aged 6 to 8 years training in taekwondo at Dojang Balai Gadang, Balai Gadang Village, Koto Tangah District, Padang City as many as 50 people. The sample of this study was taken as many as 15 children aged 6 to 8 years who took part in taekwondo training at Dojang Balai Gadang, Balai Gadang Village, Koto Tangah District, Padang City with purposive techniques. The technique of collecting data is purposive sampling using observation. The instrument used is an observation sheet. Gross motor skills which include indicators of agility, strength, endurance and speed. The data analysis technique used is quantitative analysis in the form of percentages. From the results of data management, it can be concluded that there was an increase in coordination, agility, endurance and gross motor strength of children at the seventh meeting from undeveloped to very well developed. Factors that influence children's gross motor development are age, gender, parental support, nutrition and training. It is recommended to parents, to be able to improve children's gross motor skills. Keywords: Gross motor skills, Taekwondo, Training